Comparative study of UV/H2O2 and UV/PMS processes for treating pulp and paper wastewater. (11th October 2022) - Wang, Liangliang; Fei, Yuchao; Gong, Chenhao; Shan, Yue; Zhang, Zhongguo; Zhang, Fengshan; Cheng, Hongshun
Abstract: Pulp and paper wastewater (PPWW) contains numerous refractory and harmful contaminants that require advanced treatment to meet the discharge criteria. This study compared the efficacy of two PPWW treatments: ultraviolet/peroxymonosulfate (UV/PMS) and ultraviolet/H2 O2 (UV/H2 O2 ) working under similar circumstances. The initial pH value, oxidant dosage, UV radiation intensity, and pseudo-first-order constant k obs were systematically studied in both systems. Optimally, the UV/PMS process produced an effluent of higher quality than the UV/H2 O2, as measured by the removal efficiencies of chemical oxygen demand (COD) in 60 min, which were 48.2 and 64.3% for the respective UV/H2 O2 and UV/PMS processes and corresponding k obs values of 0.0102 and 0.0159 min −1, respectively. Radical scavenging experiments demonstrated that OH was the primary reactive oxygen species in UV/H2 O2 process, and OH and SO4 − in the UV/PMS process. Moreover, ultraviolet-visible spectroscopy and gas chromatography coupled mass spectroscopy analyses showed that deep treatment of petroleum hydrocarbons with carbon chain lengths greater than 18 and macromolecular semi-volatile organic compounds in paper wastewater is difficult, whereas the UV/PMS process can significantly improve the removal of amides, esters, phenols, and other aromatic compounds. HIGHLIGHTS: UV/PMS is a worthwhile in-depth study to achieve more effective treatment of actual wastewater. It was difficult to completely degrade the organics in actual PPWW due to some long-chain alkanes and macromolecules containing benzene ring organic substances. Graphical Abstract